2005
DOI: 10.1021/ja0430999
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of N-Maleimido-Functionalized Hydrophilic Polymers via Copper-Mediated Living Radical Polymerization:  A Suitable Alternative to PEGylation Chemistry

Abstract: A series of alpha-functional maleimide polymethacrylates (M(n) = 4.1-35.4 kDa, PDi = 1.06-1.27) have been prepared via copper-catalyzed living radical polymerization (LRP). Two independent synthetic protocols have been successfully developed and the polymers obtained in multigram scale, with an 80-100% content of maleimide reactive chain ends, depending on the method employed. A method for the synthesis of amino-terminated polymers, starting from Boc-protected amino initiators, has also been developed, as thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
376
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(382 citation statements)
references
References 28 publications
5
376
0
Order By: Relevance
“…The results showed that conjugation ratios of 10:1 did not decrease the specific cytotoxic activity of the IT and that the development of an anti-IT Ab response in mice was partly suppressed by PEG conjugation, despite incomplete PEGylation. These results are consistent with the effects of PEGylation on other therapeutic proteins (32)(33)(34). Other approaches to limit immunogenicity have also been proposed (35)(36)(37)(38)(39)(40).…”
Section: Studies In Macaquessupporting
confidence: 85%
“…The results showed that conjugation ratios of 10:1 did not decrease the specific cytotoxic activity of the IT and that the development of an anti-IT Ab response in mice was partly suppressed by PEG conjugation, despite incomplete PEGylation. These results are consistent with the effects of PEGylation on other therapeutic proteins (32)(33)(34). Other approaches to limit immunogenicity have also been proposed (35)(36)(37)(38)(39)(40).…”
Section: Studies In Macaquessupporting
confidence: 85%
“…Finally, the copolymer molecular weight was checked by nuclear magnetic resonance (NMR) analysis. P(OEG 10 MA) 20 -PDPA 100 copolymer synthesis The protected maleimide initiator (Mal-Br) was prepared according to a previously published procedure (51). In a typical procedure, either ME-Br or Mal-Br initiators or ATRP initiators (0.105 mmol, 1 equiv.)…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, these polymers may be synthesized using straightforward controlled radical polymerization techniques such as atom transfer radical polymerization (ATRP) [36,37] or reversible addition-fragmentation transfer polymerization (RAFT) [38][39][40], but also functionalized using versatile ligation tools such as click chemistry [41][42][43][44]. Thus, they can be easily connected to a wide variety of materials, including planar inorganic substrates (e.g., gold or glass surfaces) [45][46][47], solid or soft-matter nanoparticles (e.g., micelles, vesicles) [48][49][50][51][52] or biological structures (e.g., proteins) [53][54][55][56][57][58]. Moreover, their thermoresponsive properties can be precisely adjusted in a near-physiological range.…”
Section: Introductionmentioning
confidence: 99%